The Impact of Resource Efficiency on Energy Intensity and Sustainability - Ogujiuba , Kanayo; Maponya, Lethabo (International Journal of Energy Economics and Policy, 2026)
Energy intensity (EI) is a crucial metric for assessing sustainable economic performance, but its understanding and effectiveness remain subject to discussion. In the context of South Africa's Water–Energy–Food (WEF) nexus, this study empirically investigates the relationship between resource efficiency and energy intensity (EI), highlighting the transitional dynamics of the country's Just Energy Transition. The study examines the short- and long-term impacts of water productivity (LWP), water withdrawal intensity (LWWI), electricity production from renewable sources (EPRS), and cereal yield (CY) on energy intensity using the Autoregressive Distributed Lag (ARDL) approach and annual time-series data covering 1990–2023. The results show that these variables have a statistically significant long-term cointegrating relationship. A higher energy intensity is linked to both short- and long-term increases in renewable electricity generation, which reflects transitional inefficiencies in early-stage renewable integration. On the other hand, reductions in water withdrawal intensity dramatically reduce energy intensity, highlighting the significance of water-use efficiency in reducing pressures on energy demand. The statistically insignificant effects of agricultural yield and water productivity point to structural heterogeneity and compensatory mechanisms in South Africa's resource systems. The results indicate that the Just Transition needs to consider the shifting trade-offs between efficiency and decarbonization, necessitating social inclusion, institutional collaboration, and technological advancements. Policy implications include boosting inter-sectoral governance mechanisms, encouraging water-efficient technologies, and improving grid flexibility. Quantifying resource interdependencies that influence sustainable energy transitions in emerging economies adds to the empirical discussion of the WEF nexus.